Reálné rozdělení administrativní budovy v Brně - Soukupová, Ivona (Vysoké učení technické v Brně. Ústav soudního inženýrství, 2016)
Předmětem diplomové práce je posouzení možnosti reálného rozdělení administrativní budovy v Brně, jako řešení vypořádání spoluvlastnictví mezi spoluvlastníky. V teoretické části práce jsou shrnuty důležité pojmy vztahující se k tématu, možnosti vypořádání spoluvlastnictví, předpoklady reálného rozdělení a oceňovací postupy. V praktické části je popsána administrativní budova a posouzena na možnost reálného rozdělení. Je provedeno ocenění administrativní budovy před jejím rozdělením, vyčíslení výše nákladů na reálné rozdělení a ocenění nově vzniklých nemovitých věcí po rozdělení dle výše vlastnických podílů. V závěru práce je navrženo vypořádání podle výše vlastnických podílů.

The aim of this master thesis is assessing the possibility of a real division of the office building in Brno as a solution of the settlement of ownership of property among the co-owners. Firstly, in the theoretical part of the study, important terms which are related to the topic are summarised, and also possibilities of settlement of co-ownership, assumptions of the real estate division and approach of valuation are handled. Secondly, in the practical part of the thesis, the description of the office building and assessment of possibility of real division in all aspects are provided. Moreover, the valuation of the office building before the division is discussed, as well as quantification of the height of costs for real division and valuation of newly established immovable properties after the division based on proprietary proportions. The study is finished with the suggestion of settlement according to the amount of proprietary proportions.
Actual division of office building in Brno
Keywords: Reálné rozdělení nemovité věci; podílové spoluvlastnictví; vypořádání spoluvlastnictví; ocenění; návrh rozdělení; položkový rozpočet.; The real estate division; co-ownership; settlement of co-ownership; valuation; design division; itemized budget.